2011
DOI: 10.1103/physrevb.83.113301
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance in a high-mobility two-dimensional electron gas

Abstract: In a high-mobility two-dimensional electron gas (2DEG) in a GaAs/Al 0.3 Ga 0.7 As quantum well we observe a strong magnetoresistance. In lowering the electron density, the magnetoresistance gets more pronounced and reaches values of more than 300%. We observe that the huge magnetoresistance vanishes when increasing the temperature. An additional density-dependent factor is introduced to be able to fit the parabolic magnetoresistance to the electron-electron interaction correction. Since the first observation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
110
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 21 publications
8
110
3
5
Order By: Relevance
“…In the range of magnetic fields corresponding to the resistivity minimum at zero bias, the resistivity increases linearly with current and the rate of this increase scales with the inverse magnetic field. The latter observation is consistent with the theory, proposed more than 35 years ago, considering classical memory effects in the presence of strong, dilute scatterersThe interest to low-field magnetotransport in twodimensional electron systems (2DES) has been recently revived owing to several experiments reporting unexpectedly strong negative magnetoresistance in GaAs/AlGaAs heterostructures [1][2][3][4][5][6][7][8]. One prominent example is the observation of a colossal negative magnetoresistance (CNMR), which is marked by a sharp drop of the resistivity ρ(B) followed by a saturation at the magnetic field…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In the range of magnetic fields corresponding to the resistivity minimum at zero bias, the resistivity increases linearly with current and the rate of this increase scales with the inverse magnetic field. The latter observation is consistent with the theory, proposed more than 35 years ago, considering classical memory effects in the presence of strong, dilute scatterersThe interest to low-field magnetotransport in twodimensional electron systems (2DES) has been recently revived owing to several experiments reporting unexpectedly strong negative magnetoresistance in GaAs/AlGaAs heterostructures [1][2][3][4][5][6][7][8]. One prominent example is the observation of a colossal negative magnetoresistance (CNMR), which is marked by a sharp drop of the resistivity ρ(B) followed by a saturation at the magnetic field…”
supporting
confidence: 69%
“…The interest to low-field magnetotransport in twodimensional electron systems (2DES) has been recently revived owing to several experiments reporting unexpectedly strong negative magnetoresistance in GaAs/AlGaAs heterostructures [1][2][3][4][5][6][7][8]. One prominent example is the observation of a colossal negative magnetoresistance (CNMR), which is marked by a sharp drop of the resistivity ρ(B) followed by a saturation at the magnetic field B ≈ B ⋆ ≈ 1 kG, close to ρ ⋆ ≡ ρ(B ⋆ ) 0.1ρ 0 , at temperature T 1 K [7].…”
mentioning
confidence: 99%
“…(3). Finally, we mention a recently reported negative magnetoresistivity effect 55,56 which occurs in the same range of magnetic fields and is strongly temperature dependent. Unfortunately, separating all these contributions does not appear feasible at this point.…”
mentioning
confidence: 99%
“…Therefore, we must conclude that, in some way, the two physical phenomena have to be connected or share the same physical origin. The first experiment to obtaine NGMR, (without irradiation) was carried out by Paalanen et al [20] and later on by Bockhorn et al [21], where they study the dependence of NGMR on temperature and electron density. Next, Y. Dai et al [22], reported on the dependence of NGMR on an in-plane B.…”
mentioning
confidence: 99%
“…For the experimental parameters that we are dealing with [21][22][23], we have estimated that ξ DC ∼ 1 − 2 V/m. On the other hand for low B ∼ 0.04 − 0.05 T, we have obtained that, in average, in the advanced distance corresponding to a scattering jump, the LL are tilted an energy ∆ ≃ 3.10 −5 eV.…”
mentioning
confidence: 99%